Indian Survey on Management of Choledocholithiasis—Opportunities for Improvement and Future Studies - Jagtap, Nitin; Waghmare, Sudatta; Sundaram, Sridhar; Khairatkar, Rohan; Modak, Shreeyash; Lakhtakia, Sundeep; Tandan, Manu; Rao, G. Venkat; Reddy, D. Nageshwar (Journal of Digestive Endoscopy, 2022)
Background In clinical practice, decision about management of choledocholithiasis is driven by availability of resources and expertise, patients and healthcare professional preferences. This survey is aimed to describe the approach of physicians and surgeons for the management of choledocholithiasis.Method A 36-question online survey was conducted using Google Forms on various aspects of management of choledocholithiasis.Results The responses from 323 participants were included, of which 202 (62.54%) were physicians and 121 (37.46%) were surgeons. The proportion of responders who do not follow American or European Society of Gastrointestinal Endoscopy guidelines is associated with increasing age and experience of responders (p = 0.0001), while place of work (private vs. teaching) and broad specialty (physician vs surgeon) are not associated (p >0.05). For patients with high likelihood of choledocholithiasis, 123 (38.1%) participants prefer to do endoscopic ultrasound/magnetic resonance cholangiopancreatography (EUS/MRCP) rather than directly performing endoscopic retrograde cholangiopancreatography/intraoperative cholangiography (ERCP/IOC). For intermediate likelihood, MRCP is more commonly preferred compared with EUS, due to local availability (44%), expertise (39.6%), healthcare professionals preference (30.7%), and patients preference (17.3%). For difficult common bile duct (CBD) stones, short biliary sphincterotomy with large balloon sphincteroplasty (59.4%), followed by laparoscopic CBD exploration are commonly used approaches. Prophylactic CBD stent placement after ERCP and CBD clearance is common practice. Preoperative ERCP followed by cholecystectomy is more preferred approach than cholecystectomy and CBD exploration.Conclusion There is considerable variability in the management of choledocholithiasis. The practices such as use of EUS/MRCP for high likelihood group, use of prophylactic CBD stent placement after ERCP and CBD clearance, and use of single stage approach especially in patient with intermediate likelihood group should be addressed in future studies.
Keywords: choledocholithiasis; guidelines; clinical practice; risk stratification; survey